Petrology and geochemistry of alteration types within a multiphase system and implications for the presence of a porphyry root, Harrison Pass Pluton, Nevada - Racosky, Alexandra, author; Ridley, John, advisor; Sutton, Sally, committee member; Bareither, Christopher, committee member (Colorado State University. Libraries, 2017)
To view the abstract, please see the full text of the document.